150k views
4 votes
Solve for d.

6(d+1)−2d=54

User Dnozay
by
5.2k points

2 Answers

0 votes

To solve this for d, first distribute 6 into the values in the parentheses.

6(d+1)-2d=54

6d+6-2d=54

Then, combine like terms (add 6d+(-2d).

6d+6-2d=54

4d+6=54

Subtract 6 from both sides.

4d+6-6=54-6

4d=48

Divide both sides by 4 for d.


(4d)/(4)=
(48)/(4)

d=12

User Humbleice
by
4.5k points
3 votes

Answer:

12

Explanation:

6(d+1)−2d=54

Here, we have to find the value of d

multiply (d+1) by 6

6×d + 6×1 - 2 d= 54

6d + 6 - 2d= 54

Now subtract 2 d from 6d

6d- 2d +6= 54

4 d+ 6=54

Now, by using transposition method,

+ 6 will be transferred from L.H.S to -6 to R.H.S

4 d = 54- 6

4d= 48

Now, divide 48 by 4

d= 48÷ 4

d= 12

Hence, the value of d is 12

Hence, the correct answer is 12

User Shauno
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.